In-vivo effects of knocking-down metabotropic glutamate receptor 5 in the SOD1G93A mouse model of amyotrophic lateral sclerosis. (1st September 2017) - Bonifacino, Tiziana; Cattaneo, Luca; Gallia, Elena; Puliti, Aldamaria; Melone, Marcello; Provenzano, Francesca; Bossi, Simone; Musante, Ilaria; Usai, Cesare; Conti, Fiorenzo; Bonanno, Giambattista; Milanese, Marco
Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder due to loss of upper and lower motor neurons (MNs). The mechanisms of neuronal death are largely unknown, thus prejudicing the successful pharmacological treatment. One major cause for MN degeneration in ALS is represented by glutamate(Glu)-mediated excitotoxicity. We have previously reported that activation of Group I metabotropic Glu receptors (mGluR1 and mGluR5) at glutamatergic spinal cord nerve terminals produces abnormal Glu release in the widely studied SOD1 G93A mouse model of ALS. We also demonstrated that halving mGluR1 expression in the SOD1 G93A mouse had a positive impact on survival, disease onset, disease progression, and on a number of cellular and biochemical readouts of ALS. We generated here SOD1 G93A mice with reduced expression of mGluR5 ( SOD1 G93A Grm5 −/+ ) by crossing the SOD1 G93A mutant mouse with the mGluR5 heterozigous Grm5 −/+ mouse. SOD1 G93A Grm5 −/+ mice showed prolonged survival probability and delayed pathology onset. These effects were associated to enhanced number of preserved MNs, decreased astrocyte and microglia activation, reduced cytosolic free Ca 2+ concentration, and regularization of abnormal Glu release in the spinal cord of SOD1 G93A Grm5 −/+ mice. Unexpectedly, only male SOD1 G93A Grm5 −/+ mice showed improved motor skills during disease progression vs. SOD1 G93A mice, while SOD1 G93A Grm5 −/+ females did not. These results demonstrate that a lower constitutive level of mGluR5 has a significant positive impact in mice with ALS and support the idea that blocking Group I mGluRs may represent a potentially effective pharmacological approach to the disease. Highlights: Knocking down mGluR5 delays clinical onset and prolongs survival in SOD1 G93A mice. Knocking down mGluR5 improves motor skills in SOD1 G93A male mice only. Knocking down mGluR5 reduces motor neuron death in SOD1 G93A mice. Knocking down mGluR5 reduces microglia and astrocyte activation in SOD1 G93A mice. Knocking down mGluR5 reduces excessive glutamate release in SOD1 G93A mice.